Oxygen therapy and respiratory support strategies after the administration of a pulmonary surfactant in a neonatal intensive care unit - Valero-Ortiz, Adriana Sofía; Roa-Cubaque, Marcela América; Corredor-Gamba, Sandra Patricia; Rojas-Laverde, María del Pilar; Chaparro-Cristancho, Laura Piedad; Ibáñez-Torres, Leidy Johana; Fonseca-Moreno, Yudi Lorena (Universidad y Salud, 2023)
Introduction: The preferred ventilation and oxygen therapy strategies for preterm newborns are ventilation and alveolar oxygenation, which trigger clinical and hemodynamic changes in patients. Objective: To determine the ventilation and oxygen therapy strategies applied after the administration of a pulmonary surfactant in newborns admitted to the Neonatal Intensive Care Unit of the San Rafael Hospital of Tunja (Colombia). Materials and methods: A retrospective cross-sectional and correlational study using a non-probabilistic sampling for convenience and 172 patient records. A univariate analysis through the Wilcoxon method was used, taking into account central tendency and correlation measures. Results: Most patients were male and almost all showed pulmonary surfactant deficiency with survival. The gestational age and average weight were 30 weeks and 1,532 g, respectively. Most required invasive and non-invasive mechanical ventilation, being intermittent positive pressure ventilation and conventional nasal cannula the most commonly used ventilation and oxygenation strategies. Finally, there was a relationship between weight and gestational age with the type of pulmonary surfactant, ventilation strategies, and the clinical outcome of the newborn. Conclusions: Birth weight and gestational age were significant indicators to determine the type of pulmonary surfactant to be administered, the ventilation and oxygen therapy strategies, and the patient’s clinical outcome.